Strategy In Customizing The Menu And Online Marketing For Greenhouse Vegetarian - Tony Wibowo; Eka Meriyadi (Universitas Internasional Batam, 2024)
Green House Vegetarian is a restaurant that faced significant challenges during the pandemic. The project aimed to revitalize this establishment by redesigning its menu and enhancing its online marketing strategy. This involved updating the menu to reflect current trends and integrating with popular food delivery platforms. The project focused on improving the restaurant's appeal and accessibility, resulting in a more diverse menu, increased online visibility, and improved customer satisfaction, thereby strengthening its position in the competitive market.